Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-13T12:59:58+01:00
1. sin3x=sin4x

sin4x-sin3x=0
(rozpisujesz z wzoru na róznice sinusów)

2cos((4x+3x)/2) * sin((4x-3x)/2) =0
2cos(7x/2) * sin(x/2) = 0
cos(7x/2) = 0 lub sin(x/2) = 0

7x/2 = π/2 + kπ
x=(π+2kπ)/7

lub

x/2 = kπ
x=2kπ



2. cos5x-cos(x-π/3)=0

(tu również z wzoru, tym razem na różnicę cosinusów)

-2sin((5x+x-π/3)/2) * sin((5x-x+π/3)/2) = 0
-2sin(3x-π/6) * sin(2x+π/6) = 0 / :(-2)

3x-(π/6) = kπ
3x = kπ- (π/6)
x= kπ/3 - π/18


lub
2x+π/6 = kπ
2x=kπ-π/6
x= kπ/2 - π/12
1 5 1